2017
DOI: 10.1016/j.bbr.2017.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress and later peer distress on depressive behavior in adolescent female rats: Effects of a novel intervention on GABA and D2 receptors

Abstract: Early life adversity (ELA) increases the risk of depression during adolescence that may result from a decline in parvalbumin (PVB) secondary to increased neuroinflammation. In this study, we investigated depressive-like behavior following exposure to two different types of stressors that are relevant for their developmental period: 1) chronic ELA (maternal separation; MS) and 2) an acute emotional stressor during adolescence (witnessing their peers receive multiple shocks; WIT), and their interaction. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 67 publications
(106 reference statements)
6
53
2
Order By: Relevance
“…Nevertheless, although there is no previous data regarding social behaviour during adolescence in MSEW mice, there is evidence showing that social defeat stress seriously affects social behaviour and induces significant social avoidance in adolescent mice (Iñiguez et al, 2014). Such data support the view that maternal separation is a well-established animal model of early life stress to develop depression-like behaviour, as despair-behaviour and social anxiety are two core symptoms of depression (Lukkes et al, 2017;Millstein and Holmes, 2007).…”
Section: Maternal Separation Produced Persistent Alterations In Emotimentioning
confidence: 67%
See 1 more Smart Citation
“…Nevertheless, although there is no previous data regarding social behaviour during adolescence in MSEW mice, there is evidence showing that social defeat stress seriously affects social behaviour and induces significant social avoidance in adolescent mice (Iñiguez et al, 2014). Such data support the view that maternal separation is a well-established animal model of early life stress to develop depression-like behaviour, as despair-behaviour and social anxiety are two core symptoms of depression (Lukkes et al, 2017;Millstein and Holmes, 2007).…”
Section: Maternal Separation Produced Persistent Alterations In Emotimentioning
confidence: 67%
“…Previous studies have shown that maternal separation affects the formation of neuronal networks and exerts long-lasting effects on neural function (Nishi et al, 2014). Moreover, maternal separation leads to high levels of anxiety-like behaviour and high stress hormone responsiveness, depression-like behaviour assessed as anhedonia, despair behaviour and a decrease in behavioural responses to novelty (George et al, 2010;Gracia-Rubio et al, 2016a;Lukkes et al, 2017;Matthews and Robbins, 2003;Rüedi-Bettschen et al, 2004). In addition, maternal separation decreases neurogenesis (Lajud et al, 2012), reduces 5-HT1A receptor levels (Bravo et al, 2014;Gracia-Rubio et al, 2016b), and increases pro-inflammatory cytokines levels in serum (Réus et al, 2015) associated with increased neuroinflammatory responses (Gracia-Rubio et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Like in mouse models, the results in rat models also varied. Increased and decreased anxiety-related behaviors, increased depression-like behaviors, or no effect on anxiety-related and depression-like behaviors were all reported (Banqueri et al, 2017;Bian et al, 2015;Leussis et al, 2012;Lukkes et al, 2017;Wang et al, 2015;Yoo et al, 2012). The inconsistency may result from variable MS protocols used in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…In adolescent C57BL/6 mice, some studies indicated that MS enhanced anxiety‐related and depression‐like behaviors (Bian et al, ), but others found it only increased anxiety‐related behaviors (Shin, Baek, Han, & Min, ; Shin, Han, Woo, Jang, & Min, ). In adolescent rats, MS has been shown to increase depressive behaviors during adolescence (Leussis, Freund, Brenhouse, Thompson, & Andersen, ; Lukkes, Meda, Thompson, Freund, & Andersen, ). However, reduced anxiety and depressive behaviors in adolescence after MS were also reported (Kwak et al, ; Wang, Li, Du, Shao, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation